A Study on the Impact of Protestant Faith as an Informal Institution on the Economy: Implications for China’s Sustainable Economic Development in the New Normal - PAN Yixing (Journal of Research for Christianity in China (JRCC), 2025)
Research on informal institutions in economic development is currently a hot topic in academia. Given that religious beliefs permeate and influence numerous aspects of informal institutions, this study holds significant importance. This paper first reviews the impact of informal institutions on economic development, highlighting their crucial role and far-reaching effects. However, it notes that academic research on informal institutions—particularly concerning religious beliefs—remains scarce. Subsequently, this paper focuses on examining the economic impact of Protestant Christian beliefs as an informal institution. Through three dimensions—work ethic, contractual spirit, and market ideology—it investigates the mechanisms and channels through which Protestant beliefs influence the economy. The conclusion drawn is that Protestant beliefs, as an informal institution, exert a positive driving force on economic development. Finally, based on the findings of this study and in light of China’s national conditions, recommendations and insights for China’s economic development under the new normal are proposed.